Multi–layered electrospinning and electrospraying approach: effect of polymeric supplements on chondrocyte suspension - Semitela, A. (2022)
Articular cartilage was expected to be one of the first tissues to be successfully engineered, but replicating the complex fibril architecture and the cellular distribution of the native cartilage has proven difficult. While electrospinning has been widely used to reproduce the depth–dependent fibre architecture in 3D scaffolds, the chondrocyte-controlled distribution remains an unsolved problem. To incorporate cells homogeneously through the depth of scaffolds, a combination of polymer electrospinning and cell seeding is necessary. A multi-layer approach alternating between polymer electrospinning with chondrocyte electrospraying can be a solution. Still, the success of this process is related to the survival rate of the electrosprayed chondrocytes embedded within the electrospun mesh. In this regard, the present study investigated the impact of the multi-layered process and the supplementation of the electrospray chondrocyte suspension with different concentrations of Gelatin and Alginate on the viability of electrosprayed chondrocytes embedded within a Polycaprolactone/Gelatin electrospun mesh and on the mechanical properties of the resulting meshes. The addition of Gelatin in the chondrocyte suspension did not increase significantly (p > 0.05) the percentage of viable electrosprayed chondrocytes (25 %), while 3 wt% Alginate addition led to a significant (p < 0.05) increase in chondrocyte viability (50 %) relative to the case without polymer supplement (15 %). Furthermore, the addition of both polymer supplements increased the mechanical properties of the multi–layer construct. These findings imply that this multi-layered approach can be applied to cartilage TE allowing for automated chondrocyte integration during scaffolds creation.